Nanoemulsion-based nasal in situ gel of olanzapine - Zahraa H Ali; Myasar Alkotaji (Journal of excipients and food chemicals, 2023)
Oral delivery of olanzapine suffers from low oral bioavailability and there has been reports of metabolic side effects. This study aimed to prepare a nanoemulsion of olanzapine and incorporate it into an in situ gel for nasal delivery. Such nasal delivery of olanzapine could provide prolonged contact time with the nasal mucosa and a potential enhanced action with lower side effects. Several formulations of nanoemulsions were prepared and characterized through the measurements of conductivity, transmittance, pH, viscosity, hydrodynamic diameter, polydispersity index, Zeta potential, entrapment efficiency, and release profiles. In addition, a pharmacodynamics study was conducted through animal studies. The selected formulation showed excellent nanoemulsion with a size in the nanometre range, a good polydispersity index with acceptable stability as indicated by the thermodynamic stability test. The cumulative percentage of olanzapine released from the nanoemulsion showed a good release profile. Pharmacodynamics study on rats using Paw test demonstrated a very clear enhancement in the anti psychotic efficacy of olanzapine in the following order: Nanoemulsion-based in situ gel (with HPMC) > nanoemulsion based in situ gel > nanoemulsion > solution. Interestingly, olanzapine from the nanoemulsion-based in situ gel showed comparable antipsychotic efficacy to haloperidol, when given intraperitoneally. Nanoemulsion based nasal in situ gel is a promising drug delivery system for olanzapine for achieving a targeted delivery. However, further investigations on olanzapine accumulation in the brain after such delivery are recommended.